2013
DOI: 10.3892/ol.2013.1195
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopamine is a novel Hedgehog signaling inhibitor with significant anti-proliferative, anti-invasive and anti-estrogenic potency in human breast cancer cells

Abstract: Stimulation of Hedgehog (Hh) signaling induces carcinogenesis or promotes cell survival in cancers of multiple organs. In epithelial cancer with aberrant Hedgehog activation, abrogation of Hedgehog signaling by cyclopamine, a naturally occurring Hedgehog-specific small-molecule inhibitor, causes profound inhibition of tumor growth. In the present study, cyclopamine displayed a significant potency in suppressing the proliferation of both estrogen-responsive (MCF-7) and estrogen-independent (MDA-MB-231) human br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 10 publications
3
38
0
Order By: Relevance
“…Cyclopamine has been demonstrated to exert effects on numerous types of tumor, including lung, ovarian, and breast cancer (41)(42)(43). However, poor oral solubility hinders its clinical development.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclopamine has been demonstrated to exert effects on numerous types of tumor, including lung, ovarian, and breast cancer (41)(42)(43). However, poor oral solubility hinders its clinical development.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is partially prevented by UO126, indicating that HH pathway inhibition requires an active MEK1/2-ERK1/2 module to produce a decrease in proliferation [120].…”
Section: Breast Cancermentioning
confidence: 98%
“…E-cadherin is a hallmark molecule of the EMT process, and its downregulation indicates enhanced cell motility (23). SLUG is a downstream target of Shh-Gli signaling, and is suggested to serve key roles in the EMT process (13). In the current study, western blotting demonstrated that 72 h treatment of MDA-MB-231 cells with human sonic hedgehog, n-terminus (N-Shh) significantly reduces E-cadherin protein levels (Fig.…”
Section: Shh Signaling Pathway Induces Mda-mb-231 Migration Through Tmentioning
confidence: 83%
“…Research indicates that cyclopamine inhibits the Hh signaling pathway by antagonizing Smo (11). In vitro and in vivo experiments have demonstrated the suppressive effects of cyclopamine on cancer cell growth (12,13).…”
Section: Introductionmentioning
confidence: 99%